Genome-wide identification of high-affinity nitrate transporter 2 (NRT2) gene family under phytohormones and abiotic stresses in alfalfa (Medicago sativa) - Yanyan Luo; Lili Nan (Scientific Reports, 2024)
Abstract The high-affinity nitrate transporter 2 (NRT2) protein plays an important role in nitrate uptake and transport in plants. In this study, the NRT2s gene family were systematically analyzed in alfalfa. We identified three MsNRT2 genes from the genomic database. They were named MsNRT2.1-2.3 based on their chromosomal location. The phylogenetic tree revealed that NRT2 proteins were categorized into two main subgroups, which were further confirmed by their gene structure and conserved motifs. Three MsNRT2 genes distributed on 2 chromosomes. Furthermore, we studied the expression patterns of MsNRT2 genes in six tissues based on RNA-sequencing data from the Short Read Archive (SRA) database of NCBI, and the results showed that MsNRT2 genes were widely expressed in six tissues. After leaves and roots were treated with drought, salt, abscisic acid (ABA) and salicylic acid (SA) for 0–48 h, and we used quantitative RT-PCR to analyze the expression levels of MsNRT2 genes and the results showed that most of the MsNRT2 genes responded to these stresses. However, there are specific genes that play a role under specific treatment conditions. This result provides a basis for further research on the target genes. In summary, MsNRT2s play an irreplaceable role in the growth, development and stress response of alfalfa, and this study provides valuable information and theoretical basis for future research on MsNRT2 function.